Odpowiedź :
[tex] \frac{1}{8} + \frac{2}{5} = \frac{5}{40} + \frac{10}{40} = \frac{15}{40} [/tex]
[tex] \frac{3}{7} - \frac{ 1}{3} = \frac{9}{21} + \frac{7}{21} = \frac{16}{21} [/tex]
[tex]1 \frac{2}{5} + 1 \frac{1}{3} = 1 \frac{6}{15} + 1 \frac{5}{15} = 1 \frac{11}{15} [/tex]
[tex]7 \frac{1}{4} - 2 \frac{1}{3} = 7 \frac{3}{12} - 2 \frac{4}{12} = \frac{59}{12} [/tex]
[tex]1 \frac{2}{3} + 2 \frac{3}{4} = 1 \frac{8}{12} + 2 \frac{9}{12} = 4 \frac{5}{12} [/tex]
[tex]4 \frac{3}{5} - 2 \frac{5}{8} = 4 \frac{24}{40} - 2 \frac{25}{40} = \frac{79}{40} [/tex]
[tex]1 \frac{3}{5} + \frac{2}{3} = 1 \frac{9}{15} + \frac{10}{15} = 2 \frac{4}{15} [/tex]
[tex]4 \frac{2}{3} - 2 \frac{2}{7} = 4 \frac{14}{21} - 2 \frac{6}{21} = 2 \frac{8}{21} [/tex]
[tex] \frac{1}{4} + \frac{1}{5} + \frac{1}{8} = \frac{10}{40} + \frac{8}{40} + \frac{5}{40} = \frac{23}{40} [/tex]